2020
DOI: 10.3390/foods9121881
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption and Scattering Properties at 900–1650 nm and Their Relationships with Soluble Solid Content and Soluble Sugars in Apple Flesh during Storage

Abstract: Soluble solid content (SSC) is regarded as the most significant internal quality associated with the taste and maturity in fruits. Evaluating the relationship between the optical properties and soluble sugars facilitates exploration of the mechanism of optical techniques in SSC assessment. In this research, absorption coefficient (μa) and reduced scattering coefficient (μ′s) of Fuji apple during storage were obtained using automatic integrating sphere (AIS) at 905–1650 nm. Relationships between μa, μ′s and SSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The absorbance values for Beverage 2 (6% fiber) were lower than the control at 1100 nm but with decreasing wavelength, the absorbance increased. The higher absorption coefficient of the solution indicates the limited penetration depth of light as these are inversely proportional to each other (Fang et al, 2020). The UV–Vis absorption spectra revealed no significant alteration in light absorption in the 700 nm region corresponding to red region of visible spectrum, which confirms minimal changes in perception of color, as also discussed later in the section on instrumental color measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance values for Beverage 2 (6% fiber) were lower than the control at 1100 nm but with decreasing wavelength, the absorbance increased. The higher absorption coefficient of the solution indicates the limited penetration depth of light as these are inversely proportional to each other (Fang et al, 2020). The UV–Vis absorption spectra revealed no significant alteration in light absorption in the 700 nm region corresponding to red region of visible spectrum, which confirms minimal changes in perception of color, as also discussed later in the section on instrumental color measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance values for Beverage 2 (6% fiber) were lower than the control at 1100 nm but with decreasing wavelength, the absorbance increased. The higher absorption coefficient of the solution indicates the limited penetration depth of light as these are inversely proportional to each other (Fang et al, 2020). The UV-Vis absorption spectra…”
Section: Uv-vis Absorption Spectrummentioning
confidence: 99%
“…Higher absorbance values were observed in the UV range (200–240 nm). The relative absorbance of the peak was found to increase with an increase in the concentration of sc‐FOS, reflecting monosaccharides' absorption in the near UV range (Assaker & Rima, 2019; Fang et al, 2020). This trend aligns with observations in various fruit juices (Ferrario et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Since sugars and malic acid are the main substrates for respiration in apples (Hulme and Rhodes, 1971), the soluble solids that decreased with the TA are considered to be sugars and it is logical that the SSC decreases during storage. Nevertheless, many publications have reported that SSC changed very little during refrigerated storage of at least 90 days after harvest (Fang et al, 2020;Kolniak-Ostek et al, 2014;Li et al, 2010;Shirzadeh and Kazemi, 2011). Therefore, under standard refrigeration conditions, the increase in the SSC due to dehydration and the decrease in soluble solids due to respiration were likely to be comparable.…”
Section: Discussionmentioning
confidence: 99%